Religious ceremonies to celebrate Eid al-Adha in Fatimid Egypt (358-567 AH / 968-1171 AD) - Al Sharqi مها عبدالله نجم (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research deals with religious ceremonies, by which we mean the procedures, traditions, and religious norms that took place when celebrating Eid al-Adha, as it is one of the great religious holidays for Muslims. The Fatimid state in Egypt gave it great attention. historically important, as well as being a form of political rivalry between them and their enemies. The research was divided into two introductions and a conclusion. The first topic dealt with preparing for the feast, while the second dealt with aspects of celebration, and the conclusion came to show the most important findings of the research.